Python : master the art of design patterns : ensure your code is sleek, efficient and elegant by mastering powerful Python design patterns : a course in three modules.: master the art of design patterns : ensure your code is sleek, efficient and elegant by mastering powerful Python design patterns : a course in three modules. (2016) - Phillips, Dusty; Kasampalis, Sakis; Giridhar, Chetan
No abstract available